Analisis Pengembangan Nilai Agama Dan Moral Anak Melalui Kreativitas Alat Permainan Edukatif (APE) Layang-Layang Hijaiyah - Moh. Abdan Syakuro; Hibana; Ardhana Reswari; Danang Prastyo (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Errors in using educational game tools (APE) will be fatal for early childhood development. The main objective is to analyze APE hijaiyah kites in increasing religious and moral values in early childhood. This type of research uses descriptive qualitative with a case study approach. The subjects involved in this study were 15 early childhood children, teachers, and parents of class A students. The subjects were selected as many as 15 students through observation and observation with the criteria: class A children aged 3-4 years making APE kites kite hijaiyah, and parents of students, teachers, and principals who were interviewed. The study collected data using interviews, observation, documentation studies, and identification of data with research instruments in the form of interview guides and observations. The research data were then analyzed using a qualitative descriptive analysis technique by describing the research results. The results showed that APE kite hijaiyah has an important role in improving aspects of the development of religious and moral values in early childhood because many children like APE can create a meaningful learning atmosphere and positively impact learning motivation.